2021
DOI: 10.31681/jetol.904704
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gamification on young mathematics learners’ achievements and attitudes

Abstract: This study aims to investigate the effect of gamification on fifth-grade students' academic achievements and attitudes towards mathematics course. For this purpose, the teaching process of the "fractions" as a subject of the mathematics course is equipped with gamification elements. The quasi-experimental design is preferred as the research design. Achievement test and attitude scale were used as data collection instruments. The participants of the study consisted of fifth-grade students (n = 46). The Pyramida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…The students linked their being highly engaged to their being highly motivated. The positive influence of motivation on participation and achievement has also been stated in the studies of Linnenbrink and Pintrich (2003), Saeed and Zyngier (2012) and Karamert & Vardar (2021).…”
Section: Conclusion and Suggestionsmentioning
confidence: 57%
See 1 more Smart Citation
“…The students linked their being highly engaged to their being highly motivated. The positive influence of motivation on participation and achievement has also been stated in the studies of Linnenbrink and Pintrich (2003), Saeed and Zyngier (2012) and Karamert & Vardar (2021).…”
Section: Conclusion and Suggestionsmentioning
confidence: 57%
“…When the studies on this subject in recent years are searched, some of the studies examine: the effect of gamified platforms for formative evaluation such as Kahoot (Yürük, 2019;Sanchez, Langer, Kaur, 2020;Zainuddin, Shujahat, Haruna & Chu, 2020;Göksün & Gürsoy, 2019;Öden, Bolat & Göksu, 2021), the effect of the use of gamification interfaces of LMS systems such as Classsdojo (Bozkurtlar & Samur, 2017), the effect of scoring in gamification on success (Attali & Arieli-Attali, 2015), meta-analysis studies in which gamification studies conducted in recent years (Yiğ & Sezgin, 2021;Tay, Goh, Safiena & Bound, 2022;Zang & Yu, 2022). In these and other studies, it was observed that there were studies on different variables ((reading performance (Chen, Li & Chen, 2020), motivation (Roy & Zaman, 2018;Hanus & Fox, 2015;Mert & Samur, 2018;Yildiz, Topçu, Kaymakçı, 2021), engagement (Zainuddin, Shujahat, Haruna & Chu, 2020), academic achievement (Attali & Arieli-Attali, 2015;Hanus & Fox, 2015;Karamert & Vardar, 2021), effects of badges and redeemable rewards (Ortega-Arranz, et. all., 2019;Mert & Samur, 2018)).…”
Section: Literaturementioning
confidence: 92%
“…As a whole, one of the findings of this research found that gamification can increase motivation, involvement in learning and students' academic achievements in various levels of learning even though three research papers (Cakiroglu & Guler, 2021;Karamert & Vardar, 2020;Reyssier et al, 2022) proven that gamification does not affect students' learning attitude (Karamert & Vardar, 2020) and high achievers (Cakiroglu & Guler, 2021). The balance of the formation of gamification tools includes various segments (mechanical, dynamic and aesthetic) can be said to be helpful for students to become motivated and able to engage themselves in learning, thus supporting the SDT theory emphasised in this systematic literature.…”
Section: Discussion Of the Fourth Objectivementioning
confidence: 72%
“…The students who participated in the research stated that they considered gamification practices as fun, developing a positive attitude towards the process, supporting participation in the lesson, increasing their desire to be successful, and increasing their curiosity about learning. As a matter of fact, gamification apps create a fun learning environment (Ak, 2022;Candan, 2022;Çağlar & Arkun-Kocadere, 2015;China, 2022;Dicheva et al, 2015;Ertan, 2020;Inesi, 2022;Tunga, 2016); increase participation in English lessons (Abi, 2021;Tan et al, 2018); and other lessons (Candan, 2022;Ertan, 2020;Fidan, 2016;Fotaris et al, 2016;Hamari, 2014;Hong & Masood, 2014;Inesi, 2022;Juárez & Carballo, 2016;Kırcı & Kahraman, 2019;Pesare et al, 2016;Yellow & Altun, 2016;Karamert, 2019;Candan, 2022;Karamert, 2019; In this research, students stated that gamification applications also have behavioral contributions, such as enabling tasks to be performed and increasing the ability to use technology. In fact, gamification applications have many cognitive, affective, and behavioral benefits as they provide active learning and are found to be fun and interesting by students (Ertan, 2020;Fidan, 2016).…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%